Analisis Multi-Geohazard dengan Metode Multi-Criteria Decision Analysis di Kawasan Ibu Kota Nusantara (IKN), Kalimantan Timur, Indonesia - Naufal, Muhammad Adi; Bayuaji, Giri; Absari, Hirundini Rustica; Kurniawan, Fathoni Tri (Jurnal Ilmiah Geologi PANGEA, 2024)
The relocation capital city of Indonesia from Jakarta to the Nusantara Capital City is in North Penajam Paser Regency (Sepaku District) and Kutai Kartanegara (Samboja District and parts of Loa Kulu, Loa Janan and Muara Jawa Districts), East Kalimantan Province. The emergence of new centers of activity in the region led to increased vulnerability to geological hazards. Analysis of potential geological hazards is important to identify areas that have a high risk of these threats. This study combines the concept of "multi-hazard" to determine the overall potential of geological hazards in the development area of the Nusantara Capital City using the Multi-Criteria Decision Analysis method. Based on the geological conditions and history of disaster events in Nusantara Capital City, it can be concluded that this area has three geological hazards (multi-geohazard) that have a high potential to become a disaster, namely earthquakes, landslides, and floods. The results of the multi-criteria decision analysis on each geological hazard resulted in the fact that Penajam District has a high level of geological hazard compared to other sub-districts in the Nusantara Capital City area with a hazard threat level of less than 20%. This shows that in the development of the Nusantara Capital City area can be categorized as safe.